The role of data and safety monitoring boards in implementation trials: When are they justified?. Issue 3 (5th June 2020) - Fiscella, Kevin; Sanders, Mechelle; Holder, Tameir; Carroll, Jennifer K.; Luque, Amneris; Cassells, Andrea; Johnson, Brent A.; Williams, Stephen K.; Tobin, Jonathan N.
Abstract: The National Institutes of Health requires data and safety monitoring boards (DSMBs) for all phase III clinical trials. The National Heart, Lung and Blood Institute requires DSMBs for all clinical trials involving more than one site and those involving cooperative agreements and contracts. These policies have resulted in the establishment of DSMBs for many implementation trials, with little consideration regarding the appropriateness of DSMBs and/or key adaptations needed by DSMBs to monitor data quality and participant safety. In this perspective, we review the unique features of implementation trials and reflect on key questions regarding the justification for DSMBs and their potential role and monitoring targets within implementation trials.